ROGER FOWLER'S CRITICAL DISCOURSE MODEL IN NEWS TEXTS ON MEDIA LIPUTAN6.COM - WIATI, RESTU PUJI RAHMAT; HASIM, ABDUL; HARYADI, ARDI MULYANA (English Literature Department, Faculty of Economics, Law, and Humanities, 2023)
Abstract: This study aims to analyze news texts in Liputan6.com media through Roger Fowler's critical discourse analysis model. The background of this research was carried out as a form of researchers' anxiety about the development of information in digital media. Discourse has a great influence in conveying information on events that occur in society so this research needs to be done. This model is divided into two parts, namely vocabulary and grammar. The theory used is that vocabulary makes classifications and vocabulary limits view. Grammar affects the form of the passive voice and the interpretation that occurs in the news. This research is descriptive in nature. This research design was chosen because through this research it is possible to get an overview of how media build media. The data taken in this study is qualitative data, namely data in the form of news text from the online media Liputan6.com. The selected news is only news about news that occurs in the community. The results of this study indicate (1) The use of limiting words in five news stories, namely there are eighteen words that limit views and are invited to think about understanding the news. (2) The use of passive sentence grammar contained in the five news stories, namely there are seven effect passive sentences which contain the information obtained or the meaning produced in the news. (3) There are five interpretations of the news which have their own views in expressing all matters related to the information to be conveyed.